KELAYAKAN FINANSIAL DAN PENDAPATAN USAHA BUDIDAYA IKAN PATIN STUDI KASUS DI CV XYZ KECAMATAN BUMI RATU NUBAN KABUPATEN LAMPUNG TENGAH - Vivi Ayu Yuliana; Fembriarti Erry Prasmatiwi; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
Patin fish culture requires a large amount in terms of cost in its implementation. This study aims to analyze business performance financial, production,  and marketing aspects. The research method used is a case study in CV XYZ in Central Lampung District conducted in May-June 2019. Measurement of business performance from a financial aspect uses NPV, IRR, Net B / C, Gross B / C, and Payback Period with 12% interest rate. Measurement of business performance from the aspect of production uses the calculation of productivity and income during season one and season two. The study concludes that the patin fish culture business per 1,000 m2 was profitable to run, seen from the IRR value at 13.06%, NPV at 22,671,483.98, Net B/C at 1.05, Gross B/C at 1.01, and Payback Period at 7.67.  The patin fish culture business from the aspect of production has been profitable based on the productivity obtained, namely per pond of 1.000 kg in season one and 750 kg in season two, per hectare at 50,000 kg in season one and 37,500 kg in season two.Key words: financial, income, patin fish